2017
DOI: 10.1371/journal.pone.0185863
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome sequencing of two cultivated jute species under salinity stress

Abstract: Soil salinity, a major environmental stress, reduces agricultural productivity by restricting plant development and growth. Jute (Corchorus spp.), a commercially important bast fiber crop, includes two commercially cultivated species, Corchorus capsularis and Corchorus olitorius. We conducted high-throughput transcriptome sequencing of 24 C. capsularis and C. olitorius samples under salt stress and found 127 common differentially expressed genes (DEGs); additionally, 4489 and 492 common DEGs were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(47 reference statements)
2
19
0
Order By: Relevance
“…In this study, the expression of PYL4 was downregulated, while PP2Cs and SAPK3 were both upregulated; PP2Cs and SAPK3 displayed the same expression trends in both drought-stressed and ABA-treated hemp plants. Similar findings were also reported in drought- or salinity-stressed tomato and jute plants [ 23 , 61 ] and ABA-treated tomato plants [ 62 ]. Additionally, a gene encoding PYL4 was also downregulated in drought-stressed potato plants [ 30 ]; CsPYL3 was downregulated, although CsPYL1 , CsPYL2 , CsPP2C2 , and CsSnKR2.2 were upregulated in roots and stems of cucumber seedlings under drought conditions [ 63 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the expression of PYL4 was downregulated, while PP2Cs and SAPK3 were both upregulated; PP2Cs and SAPK3 displayed the same expression trends in both drought-stressed and ABA-treated hemp plants. Similar findings were also reported in drought- or salinity-stressed tomato and jute plants [ 23 , 61 ] and ABA-treated tomato plants [ 62 ]. Additionally, a gene encoding PYL4 was also downregulated in drought-stressed potato plants [ 30 ]; CsPYL3 was downregulated, although CsPYL1 , CsPYL2 , CsPP2C2 , and CsSnKR2.2 were upregulated in roots and stems of cucumber seedlings under drought conditions [ 63 ].…”
Section: Discussionsupporting
confidence: 87%
“…High-throughput sequencing has become a powerful tool in many research fields due to its cost-efficiency and rapidness [ 17 23 ]. The data yielded facilitates the development of genetic analyses and functional genomics studies among species, especially for many nonmodel plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies of salt tolerance in jute have focused only on the morphological, physiological, and proteomic components [26]. To our knowledge, only two studies [9, 27] related to the salt tolerance of jute have been carried out through transcriptome sequencing, revealing a large number of differentially expressed genes underlying salt tolerance. However, the large number of differentially expressed genes made it difficult to identify the best candidate genes related to salt tolerance for practical application.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the possible salt-stress-responsible gene, Yang et al [ 71 ] reported that, along with different transcription factors, a smaller amount of differentially expressed unigenes (DEGs) were implicated in different metabolic traits that enhanced stress tolerance in jute, such as the ABA signaling pathway, plant hormone signal transduction, and metabolism of cystine/methionine, and these were mainly noticeable in the root tissue of salt-tolerant genotypes. Similarly, another three relevant pathways enriched in root, namely, Ca 2+ - and mitogen-activated protein kinase signaling pathways and oxidative phosphorylation pathways, were identified by Yang et al [ 72 ], which were involved in the mechanism of salt stress tolerance in two jute species ( C. capsularis and C. olitorius ).…”
Section: Genetic Approaches In Enhancing Jute Tolerance To Abiotic Stressmentioning
confidence: 99%